Amour fou and Crazy in love? - Schleich, Markus (Primerjalna književnost, 2014)
Amour Fou is a universal literary topos, which originates in ancient Greece and survived until the beginning of the 20th century. It lost a lot of its attraction within the context of postmodernism, medical findings and popular culture. This paper seeks to explore its re-emergence within a new visual media.
Keywords: postmodernizem; popularna kultura; intermedialnost; ljubezen; love; strast